PENGGUNAAN MEDIA YOUTUBE DALAM PEMBELAJARAN PAI DI SEKOLAH DASAR - Munawir; Jannah, Shofiyah Wardatul; Putri, Alifia Selviana Agnie (INOVATIF: Jurnal Penelitian Pendidikan, Agama, dan Kebudayaan, 2024)
This research aims to see the effectiveness of using YouTube media in PAI learning at school. This type of research is qualitative and uses data collection techniques in the form of interviews and observations. The results of this research are that the use of social media helps students improve their learning abilities. Enthusiasm for studying the material presented by the teacher, especially PAI learning which is full of moral and religious values. Social media platforms like YouTube are now very popular among the general public, including children. Social media plays an important role in making it easier for people to communicate and obtain information. YouTube is a popular application that is widely used by people today. Social media can not only be used for games but to promote learning activities anytime and anywhere. YouTube makes it very easy to access and provides audiovisual features that can be used instead.